2016
DOI: 10.3892/etm.2016.3773
|View full text |Cite
|
Sign up to set email alerts
|

Kai-Xin-San, a traditional Chinese medicine formulation, exerts antidepressive and neuroprotective effects by promoting pCREB upstream pathways

Abstract: Kai-Xin-San (KXS) is a traditional Chinese medicine that has been widely used for the treatment of emotion-related disease. However, the underlying mechanism remains largely unknown. The present study aimed to examine whether phospho-cAMP response element-binding protein (pCREB) and upstream components, such as extracellular signal-regulated kinase (ERK), phospho-ERK (pERK), phosphatidylinositol-3-kinase (PI3K), protein kinase B (Akt), glycogen synthase kinase 3β (GSK3β) and pGSK3β are associated with the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…The application of the KXS formula has been retrospected to the Tang dynasty, and the explanation of the basis of its potential pharmacodynamic material could also be achieved by modern analytical techniques [52]. At the small molecule level, the LC-Q-TOF-MS method with high resolution and sensitivity was established to analyze the transitional components of KXS in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The application of the KXS formula has been retrospected to the Tang dynasty, and the explanation of the basis of its potential pharmacodynamic material could also be achieved by modern analytical techniques [52]. At the small molecule level, the LC-Q-TOF-MS method with high resolution and sensitivity was established to analyze the transitional components of KXS in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…As an indicator of depression, 9 (23.7%) studies (Wang et al, 2007;Dang, 2008;Dong et al, 2013Dong et al, , 2016Dong et al, , 2017Liu W. W. et al, 2015;Yan et al, 2016;Zhang et al, 2016;Zhang, 2018) reported the number of rearing events in the open-field test. Kaixinsan induced a marked increase in the number of rearing events in the open-field test compared with that in the control group (P = 0.0003; SMD = 0.57, 95% CI [0.26, 0.88]; Heterogeneity: χ2 = 15.39, df = 9 (P = 0.05); I 2 = 48%, Figure 3A).…”
Section: Effectivenessmentioning
confidence: 99%
“…The pooled data showed that KXS treatment resulted in a marked drop in the duration of immobility in the forced swimming test compared with that in the control groups (P < 0.00001; SMD=-1.92, 95% CI [−2.38, −1.47]; Heterogeneity: χ2 =9.89, df = 5 (P = 0.08); I 2 = 49%, Figure 3C). Thirteen (34.2%) studies (Wang et al, 2007;Dang, 2008;Dang et al, 2009;Dong et al, 2013Dong et al, , 2016Dong et al, , 2017Huang et al, 2014;Liu W. W. et al, 2015;Fonarow, 2016;Yan et al, 2016;Dou, 2017;Zhang, 2018) evaluated sucrose consumption or sucrose preference index in the sucrose preference test. Treatment with KXS resulted in significantly different sucrose consumption or sucrose preference than that in the control group (P < 0.00001; SMD = 1.67, 95% CI [1.37, 1.97];…”
Section: Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of experimental studies and clinical observations have con rmed that Chinese medicine has unique advantages in treating IS. Various empirical prescriptions, single drugs and active ingredient extracts have been shown clear neuroprotective effects on IS [4][5][6].…”
Section: Introductionmentioning
confidence: 99%